EFFECTS OF ENALAPRIL ON ENDOTHELIUM FUNCTION IN PATIENTS WITH ISCHEMIC HEART DISEASE - L. I. Katelnizkaya; L. A. Chaischeva (Рациональная фармакотерапия в кардиологии)
Aim. To study endothelium vasomotor function (EF) in patients with ischemic heart disease (IHD) and the influence of angiotensin converting enzyme inhibitor enalapril (Enam, Dr .Reddy’s, India) on it. Material and methods. 87 patients were examined totally. 49 patients were suffering from IHD: 18 patients were younger than 60 years old and 31 patients were older . The combination of arterial hypertension (HT) and IHD were registered in 38 patients: 18 patients were below and 20 patients were above 60 years old. All patients additionally to basic IHD therapy took enalapril in dose 2,5-30 mg/daily during 12 weeks. Before the beginning and in the end of treatment cuff test, test with nitroglycerine, bicycle exercise test and Holter monitoring were made, the thickness of intima-media complex of carotid artery and the level of endothelin-1 in blood plasma were defined. Results. EF disorders were shown in IHD, maximal disorders were determined in patients with combination of IHD and HT. EF disorders were also more expressive in patients of elder group. Enalapril restored of cuff tests results, nitroglycerine tests results, reduced a number of myocardial ischemia episodes and provided target blood pressure in 60, 5% patients with HT. Conclusion. Enalapril improves endothelium vasomotor function, endothelium reaction on nitroglycerine and clinical course of IHD and HT.